OPTIMIZING UTILIZATION OF WATER IN VAN DER WIJCK IRRIGATION SYSTEM BY FUZZY LINEAR PROGRAMMING FOR FARMING SYSTEM - Sukarjo Sukarjo (Widyariset, 2011)
Van Der Wijck irrigation system was applied in Sleman and Bantul district of the Yogyakarta Special Province that has a 3,426.57 ha area. Van Der Wijck is a multipurpose irrigation system because water is used not only for growing crops, but also for sugarcane plantation and fi sh pond. Because the priority service is not clearly defi ned, confl icts among water users are easily occur. The aims of the study were (i) to compute and to predict the water availability both from rainfall and river fl ow, and (ii) to determine the use of the water in order to obtain optimum area of fi sh pond, sugarcane plantation, and other crops passed on discharge availability, seasonal water require-ment, and farm profi t. The results showed that the optimum areas for fi sh pond 17.2 ha and rice fi eld 3,309.57, 2,409.57, and 1,909.57 ha for planting season I, II, and III, respectively. The optimum areas for sugarcane are 35 ha, which is exchangeable with rice area. The optimum area of upland crops for planting season I, II, and III are 100, 1,000, and 200 ha, respectively.